2005
DOI: 10.1021/jp046127i
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Cross-Section and Related Optical Properties of Colloidal InAs Quantum Dots

Abstract: We report the absorption cross-section of colloidal InAs quantum dots of mean radii from 1.6 to 3.45 nm. We find excellent agreement between the measured results and calculated values based on a model of small-particle light absorption. The absorption cross-section per dot is 6.2 x 10(-16)R(3) cm(2) at 2.76 eV and 3.15 x 10(-16)R(1.28) cm(2) at the first-exciton absorption peak, with the dot radius R in nm. We find that the per-quantum-dot particle oscillator strength of the first-exciton transition is constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
172
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(192 citation statements)
references
References 23 publications
17
172
1
2
Order By: Relevance
“…The reason might lie in the giant oscillator strength effect predicted by the EMA which has thus not been observed consistently in quantum dot systems. [19,20,22,23] This effect predicts that the oscillator strength (per volume) of optical transitions in semiconductors would be proportional to r À3 and thus would justify such a strong oscillator strength in such diminutive structures as the ones we report here. [24] While single-wire measurements are beyond the scope of this report, the electrical properties of Bi 2 S 3 nanowire films could be easily measured and the results are shown in Figure 3.…”
mentioning
confidence: 58%
“…The reason might lie in the giant oscillator strength effect predicted by the EMA which has thus not been observed consistently in quantum dot systems. [19,20,22,23] This effect predicts that the oscillator strength (per volume) of optical transitions in semiconductors would be proportional to r À3 and thus would justify such a strong oscillator strength in such diminutive structures as the ones we report here. [24] While single-wire measurements are beyond the scope of this report, the electrical properties of Bi 2 S 3 nanowire films could be easily measured and the results are shown in Figure 3.…”
mentioning
confidence: 58%
“…In this work we have relied on the theoretical and experimental framework established by the earlier work of Brus et al (10,11,44,45), Bawendi et al (18,19,22,23,(46)(47)(48)(49) and others (15,24,25,50,51). Experimental data have shown a strong correlation between the method of dot preparation and excited state behavior (23).…”
Section: Discussionmentioning
confidence: 99%
“…For QDs like InAs, 13 wz-and zb-CdSe, 12,17 PbS, 14 PbSe, 16 and ZnO, 15 it has been shown that μ i is independent of the QD size at energies well above the band-gap energy. Within the Maxwell Garnett model, the absorption coefficient can be written in terms of the refractive index n s of the solvent and the dielectric function ε = ε R + iε I of the dispersed particles: 26…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[12][13][14][15][16][17] In Eq. (2), the local-field factor f LF gives the ratio between the (optical) electric field outside (E 0 ) and inside (E) a QD.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation